Post-Delivery Recovery Until All Women's Reproductive Organs Recover After Delivery (Postpartum Period 6 - 8 Weeks) Regarding Knowledge Of Umbilical Cord Care In Postpartum Mothers - Ernawati, Ernawati; Ula, Zumrotul; Muthoharoh, Binti Lulu; Rahmat, Rezqiqah Aulia; Saad, Rahmiyani; Devin, Devin; Wati, Isra (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The postpartum period or puerperium or postpartum period is the period or time that begins after baby born until 6 Sunday. Mother postpartum experience adaptation Which divided in the talking in phase is when the mother is in a period of dependency, focused on herself, and the mother is uncomfortable with physical changes. Talking hold phase, in this phase the mother feels worried about not being able to care for her baby. The goal of umbilical cord care is to identify early and prevent bleeding. This study is a descriptive study with the main objective to describe the knowledge of postpartum mothers about umbilical cord care. The data in this study are primary data and secondary data. Based on the results of the study of postpartum mothers' knowledge about